The Role of Coinhibitory Signaling Pathways in Transplantation and Tolerance - McGrath, Martina M.; Najafian, Nader (Frontiers in Immunology, 2012)
Negative costimulatory molecules, acting through so-called inhibitory pathways, play a crucial role in the control of T cell responses. This negative “second signal” opposes T cell receptor activation and leads to downregulation of T cell proliferation and promotes antigen specific tolerance. Much interest has focused upon these pathways in recent years as a method to control detrimental alloresponses and promote allograft tolerance. However, recent experimental data highlights the complexity of negative costimulatory pathways in alloimmunity. Varying effects are observed from molecules expressed on donor and recipient tissues and also depending upon the activation status of immune cells involved. There appears to be significant overlap and redundancy within these systems, rendering this a challenging area to understand and exploit therapeutically. In this article, we will review the literature at the current time regarding the major negative costimulation pathways including CTLA-4:B7, PD-1:PD-L1/PD-L2 and PD-L1:B7-1, B7-H3, B7-H4, HVEM:BTLA/CD160, and TIM-3:Galectin-9. We aim to outline the role of these pathways in alloimmunity and discuss their potential applications for tolerance induction in transplantation.